Improving yield, quality and economic potential of strawberries grown in high tunnels for Kansas - Mukherjee, Amrita (Kansas State University, 2022)
Interest in spring day-neutral strawberry production in high tunnels is increasing in the Midwest. Although day-neutral cultivars have a much longer fruiting period than June-bearing cultivars, it is not clear if they will thrive in the summer climatic conditions in Kansas. High temperatures can reduce fruit yield and quality, potentially resulting in poorer fruit marketability and profitability for growers. A recent study at Kansas State University saw that heat-tolerant cultivars could be grown in high tunnels in Kansas when shade cloth was used. Different colored plastic mulches could also be used to change the soil temperature and light intensity, which can help to improve productivity and fruit quality. The goal of this thesis was to determine the best color for plastic mulch for a high tunnel system in regard to productivity, fruit quality, and profitability. A split-plot randomized complete block design was used in trials conducted at the Kansas State University Olathe Horticulture Research and Extension Center in 2020 and 2021. Six plastic mulches (black, white, black stripe, silver, red, and green) were employed, as well as two-day neutral cultivars, ‘Albion’ and ‘Portola’. Throughout the season, soil temperature, UV-A, and UV-B were measured in each plastic plot. All input costs were recorded throughout the growing season to calculate the production budget and profitability of the production system based on crop price and marketability. Three harvests were analyzed for quality, and mature fruit (90% to 100% red) and fruit yield was measured by harvesting strawberry plants twice per week. At harvest and for up to four days of storage, visual quality, respiration, flesh firmness, color, soluble solids content (SSC), titratable acidity (TA), and SSC/TA ratio were measured as well as nutritional quality (total phenolic, antioxidant, and anthocyanin). In our study, total and marketable strawberry fruit yields were greater in 2020 than 2021. In comparison to the (standard) black mulch, the silver mulch had a higher fruit yield, likely due to a reduced temperature range and lower UV-B irradiation capacity (P<0.0001). Strawberries grown with silver mulch had 38 % and 33% higher total and marketable fruit weight per plant, respectively (P<0.0001). The ‘Portola’ plants grown with the green mulch had 7% higher marketability compared to the ones grown with black plastic mulch. ‘Portola’ showed significantly higher total (1.68 lb/plant) and marketable (1.04 lb/plant) yield compared to ‘Albion’, which produced 1.08 lb/plant and 0.76 lb/plant, respectively (P< 0.0001). Strawberry size, soluble solid content, SSC/TA ratio, color, firmness, and total anthocyanin content were not affected by plastic mulch color. ‘Albion’ fruit grown with silver mulch had greater TA, FRAP and total phenolics than those grown with black mulch when measured at harvest (P < 0.0001). In contrast, ‘Portola’ fruit grown with the black plastic mulch had the greatest FRAP concentration (1020 mol 100 g-1) compared to the other plastic mulch. According to our findings, the use of silver mulch enhanced yield for both cultivars and antioxidant content for ‘Albion.’ The economic analysis revealed that silver mulch was also the most profitable mulch for ‘Albion’, while the black stripe mulch performed the best for ‘Portola’, which had the lowest breakeven prices of $2.18/lb and $1.92/lb, in 2020. The average percent marketability ([marketable fruit yield / total fruit yield] x 100) observed in our trials was 69.4 %, which is estimated to provide $870/1000ft² in net revenue at $2.80/lb. When the selling price was projected at $3.02/lb for ‘Portola’ and $4/lb for ‘Albion’, it was estimated that the profit was equal to the investment cost (100% ROI). The results of this work indicate that the use of silver and other reflective mulches may be a low-cost way to effectively increase strawberry yield and quality. The economic analysis also suggests that the production of day-neutral strawberries can be a profitable enterprise for high tunnel growers in the region. As growers integrate this crop into their production system, careful consideration to the cultivar, growing methods, and marketing will be critical for success.
Keywords: Day-neutral strawberry; High tunnels